2008
DOI: 10.1080/09500690701191433
|View full text |Cite
|
Sign up to set email alerts
|

University Students’ Conceptualization and Interpretation of Topographic Maps

Abstract: This study investigates the strategies and assumptions that college students entering an introductory physical geology laboratory use to interpret topographic maps, and follows the progress of the students during the laboratory to analyze changes in those strategies and assumptions. To elicit students' strategies and assumptions, we created and refined a topographic visualization test that was administered before and after instruction to 26 students during the first semester of the study and to 92 students dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Two skills are fundamental for successful map usage: (1) knowledge of how elevation information about the terrain is encoded using contour lines (i.e., elevation information); and (2) an understanding of how the two-dimensional contour patterns on a topographic map align to three-dimensional structures in the real world (i.e., shape information). A survey of the relevant literature suggests that novices have difficulty with both of these tasks (e.g., Clark et al ., 2008; Rapp et al ., 2007). In this experiment, we use two kinds of gestures, pointing and tracing gestures and three-dimensional gestures, both helpful in understanding complex two-dimensional diagrams (e.g., Atit et al ., 2013; Atit et al ., 2015), to bolster novices’ skills.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two skills are fundamental for successful map usage: (1) knowledge of how elevation information about the terrain is encoded using contour lines (i.e., elevation information); and (2) an understanding of how the two-dimensional contour patterns on a topographic map align to three-dimensional structures in the real world (i.e., shape information). A survey of the relevant literature suggests that novices have difficulty with both of these tasks (e.g., Clark et al ., 2008; Rapp et al ., 2007). In this experiment, we use two kinds of gestures, pointing and tracing gestures and three-dimensional gestures, both helpful in understanding complex two-dimensional diagrams (e.g., Atit et al ., 2013; Atit et al ., 2015), to bolster novices’ skills.…”
Section: Methodsmentioning
confidence: 99%
“…Topographic maps are a “graphic representation of the three dimensional configuration of the earth” (Geographic Information Technology Training Alliance, 2016) and are commonly used to help gain a three-dimensional understanding of the landscape of a region (Dennis, 1972). Although frequently used by experts, these maps are particularly difficult for students to comprehend (e.g., Clark et al ., 2008; Rapp, Culpepper, Kirkby, & Morin, 2007).
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…While topographic maps have been and continue to be used for teaching cartography, researchers such as Griffin and Lock [5] found that there are inherent perceptual problems in contour line interpretation. These difficulties have generated problems of frustration/motivation among students [6][7][8][9]. Further, issues such as landform representation, spatial skills acquisition, or processes of spatial knowledge construction with different forms of relief representation continue to be active fields of research including recent works by Carbonell [10,11], Collins [12], Tillman, Albrecht and Wunderlich [13], Eynard and Bernhard [14], and Brooke and Bernhard [3].…”
Section: Introductionmentioning
confidence: 99%
“…Learning to read topographic maps is difficult (e.g. Clark et al 2008;Rapp et al 2007), yet skill with them is essential to geoscience, architecture, urban design, and landscape planning (Petcovic et al 2009), and for emergency responders, e.g., when asked to find landing sites for rescue helicopters (Wilkening & Fabrikant 2011).…”
Section: Symbolic Representation Of Topographymentioning
confidence: 99%
“…Learning to read topographic maps is difficult (e.g. Clark et al 2008;Rapp et al 2007), yet skill with them is essential to geoscience, architecture, urban design, and landscape planning (Petcovic et al 2009), and for emergency responders, e.g., when asked to find landing sites for rescue helicopters (Wilkening & Fabrikant 2011).Efforts to devise ways to facilitate acquisition of skills with topographic maps have often focused on providing additional visual information, such as various kinds of shaded relief (e.g. Phillips et al 1975;Pingel & Clarke 2014;Potash et al 1978), stereo effects (Rapp et al 2007), color-enhanced contour lines (e.g., Taylor et al 2004) or direct www.thebalticyearbook.org…”
mentioning
confidence: 99%